CARBON AND HYDROGEN ISOTOPE VARIATION OF PLANT BIOMARKERS IN A PLANT-SOIL SYSTEM - Chikaraishi Y.; Naraoka H. (My University, 2006)
Stable carbon (δ13C) and hydrogen (δD) isotopic compositions of n-alkanes, anteiso-alkanes, n-alkanoic acids, n-alkanols, phytol and sterols in raw leaves of Acer argutum and Acer carpinifolium, their fallen leaves, mold and soils from a natural Acer forest were measured in order to: (1) understand isotopic variation of the plant biomarkers in a plant-soil system and (2) evaluate which biomarker is the most effective recorder of soil vegetation. Long-chain (> C24) n-alkanes, n-alkanoic acids and n-alkanols are gradually enriched in 13C up to 12.9‰ (average of 4.3‰) and depleted in D up to 94‰ (average of 55‰) from raw leaves to soils. However, anteiso-alkanes, phytol and sterols show little variation in both δ13C (< ± 1‰) and δD (< ± 2‰) from raw leaves to soils. These isotope signatures in a plant-soil system indicate that isoprenoid plant biomarkers such as sterols in soils faithfully preserve the isotopic compositions of dominant higher plants growing on the soils without a diagenetic effect upon the isotopic compositions. In contrast, long-chain n-alkyl molecules in soils undergo specific isotopic modification during biodegradation associated with early diagenesis and/or a significant contribution from heterotrophic reworking. © 2006 Elsevier B.V. All rights reserved.
Keywords: CARBON ISOTOPIC COMPOSITION; DIAGENETIC EFFECT; HYDROGEN ISOTOPIC COMPOSITION; PLANT BIOMARKER; PLANT-SOIL SYSTEM